Mitochondria-based holistic 3PM approach as the 'game-changer' for individualised rehabilitation-the proof-of-principle model by treated breast cancer survivors - Pesta, Martin; Mrazova, Barbara; Kapalla, Marko; Kulda, Vlastimil; Gkika, Eleni; Golubnitschaja, Olga (The EPMA journal, 2024)
Breast cancer belongs to the most commonly diagnosed malignancies worldwide, with its increasing incidence paralleled by advances in early diagnostics and effective treatments resulting in significantly improved survival rates. However, breast cancer survivors often experience significantly reduced quality of life linked to the long-term health burden as a consequence of aggressive oncological treatments applied. Their most frequently recorded complains include chronic fatigue, reduced physical activity, disordered sleep, chronification of pain, and severe mental health impairments-all per evidence are associated with compromised mitochondrial health and impaired homeostasis. Self-report of a breast cancer survivor is included in this article to illustrate currently uncovered patient needs. This article highlights mechanisms behind the suboptimal health of breast cancer survivors associated with mitochondrial damage, and introduces a novel, mitochondria-based holistic approach addressing rehabilitation concepts for breast cancer survivors following advanced principles of predictive, preventive and personalised medicine (3PM). By operating via mitochondrial function, the proposed holistic approach triggers systemic effects at molecular, sub/cellular and organismal levels positively affecting energy metabolism, repair mechanisms as well as physical and mental health creating, therefore, highly effective rehabilitation algorithms tailored to an individualised patient profile. The proposed methodology integrates mitochondrial health assessments utilising mitochondrial homeostasis biomarkers in tear fluid as a non-invasive diagnostic tool, tailored nutraceuticals and lifestyle adjustments. The introduced approach aligns with advanced principles of 3PM, offering a holistic and proactive framework for managing persistent post-treatment symptoms of suboptimal health in the cohort of cancer survivors. Furthermore, presented approach is also applicable to pre-habilitation programmes considering needs of other patient cohorts affected by chronic diseases such as CVD and orthopaedic disorders with planned major surgical incisions, who require individually adapted pre- and rehabilitation programmes. Implementing such innovative pre- and rehabilitation strategies may lead to a full recovery, sustainable health conditions and, therefore, facilitating patients' comeback to normal daily activities, family and professional life. Contextually, presented approach is considered a 'proof-of-principle' model for the 3PM-related paradigm shift from reactive medicine to a cost-effective holistic health management in both primary and secondary care benefiting a large spectrum of affected patient cohorts, individuals in suboptimal health conditions as well as society at large.
Keywords: Breast cancer survivors; Health risk assessment; Mitophagy; Rehabilitation; Chronic fatigue; Homeostasis; Patient-friendly non-invasive approach; Expert recommendations; Patient self-report; Behavioural patterns; Predictive preventive personalised medicine (PPPM / 3PM); Health policy; Life quality; Sleep medicine; Individualised patient profile; Tear fluid analysis; Mitochondrial health; Secondary care; Healthcare economy